A Summary of Revisions to the Worker Protection Standard—2015 - Frederick M. Fishel (EDIS, 2016)
In 1992, the US Environmental Protection Agency (EPA) issued a comprehensive regulation called the Worker Protection Standard for Agricultural Pesticides (WPS). The WPS covers pesticides used in the outdoor and enclosed space production of plants on farms, forests, and nurseries, as well as greenhouses. The EPA has made several changes to the WPS since it was fully implemented in 1995. On November 2, 2015, the EPA revised the WPS, making significant changes to the rule’s requirements. This 5-page fact sheet explains those changes. Written by Frederick M. Fishel, and published by the Agronomy Department, December 2015.